Perceptions of the EU’s Indo-Pacific Policy in the Philippines - Patrick Ziegenhain (Andalas Journal of International Studies (AJIS), 2025)
The rise of the Indo-Pacific region as a key strategic and economic area has prompted the European Union (EU) to increase its engagement there. The EU, whose foreign policy approach is closely related to the liberalism macro theory in International Relations (IR), has thus developed a robust strategy to work more closely with Southeast Asian countries, such as the Philippines. The research question of this study is how the political elites and the general public in the Philippines perceive the EU's efforts in Southeast Asia. The research findings are that the EU is perceived positively, but awareness of the EU's foreign policy initiatives among the political elites and the general public remains relatively low. Academics and local experts underline the potential benefits of EU partnerships beyond the military dimension, which is in accordance with a traditional liberal foreign policy. However, there is criticism of the EU's perceived moral stance and capabilities in the region, with doubts about its willingness to engage militarily in regional conflicts, which would stand in contrast to a liberal foreign policy approach. Overall, while the Philippine government and general public welcomes the EU's commitment to a rules-based order in the face of Chinese encroachment, skepticism remains about the EU's strategic relevance and practical impact in safeguarding Philippine interests.